Pain Perception and Migraine - Russo, Antonio; Coppola, Gianluca; Pierelli, Francesco; Parisi, Vincenzo; Silvestro, Marcello; Tessitore, Alessandro; Tedeschi, Gioacchino (Frontiers in Neurology, 2018)
Background: It is well-known that both inter- and intra-individual differences exist in the perception of pain; this is especially true in migraine, an elusive pain disorder of the head. Although electrophysiology and neuroimaging techniques have greatly contributed to a better understanding of the mechanisms involved in migraine during recent decades, the exact characteristics of pain threshold and pain intensity perception remain to be determined, and continue to be a matter of debate. Objective: The aim of this review is to provide a comprehensive overview of clinical, electrophysiological, and functional neuroimaging studies investigating changes during various phases of the so-called “migraine cycle” and in different migraine phenotypes, using pain threshold and pain intensity perception assessments. Methods: A systematic search for qualitative studies was conducted using search terms “migraine,” “pain,” “headache,” “temporal summation,” “quantitative sensory testing,” and “threshold,” alone and in combination (subject headings and keywords). The literature search was updated using the additional keywords “pain intensity,” and “neuroimaging” to identify full-text papers written in English and published in peer-reviewed journals, using PubMed and Google Scholar databases. In addition, we manually searched the reference lists of all research articles and review articles. Conclusion: Consistent data indicate that pain threshold is lower during the ictal phase than during the interictal phase of migraine or healthy controls in response to pressure, cold and heat stimuli. There is evidence for preictal sub-allodynia, whereas interictal results are conflicting due to either reduced or no observed difference in pain threshold. On the other hand, despite methodological limitations, converging observations support the concept that migraine attacks may be characterized by an increased pain intensity perception, which normalizes between episodes. Nevertheless, future studies are required to longitudinally evaluate a large group of patients before and after pharmacological and non-pharmacological interventions to investigate phases of the migraine cycle, clinical parameters of disease severity and chronic medication usage.